Electronic Participation c - Tambouris, Efthimios; Macintosh, Ann.; Bruijn, Hans.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the Third International Conference on Electronic Participation, ePart 2011, held in Delft, The Netherlands, in August/September 2011. The 26 revised full papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on appreciation of social media; visualizing arguments; understanding eParticipation; eParticipation initiatiaves and country studies; participation and eServices; and innovative technologies.
Appreciation of social media -- visualizing arguments -- understanding eParticipation -- eParticipation initiatiaves and country studies -- participation and eServices -- innovative technologies.
Keywords: Computer science; Computer Communication Networks; Information storage and retrieval systems; Information systems; Computer Science; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl.Internet).; Computers and Society; Computer Communication Networks; User Interfaces and Human Computer Interaction; Information Storage and Retrieval